PEMBUATAN BATAKO DARI ABU HASIL INSINERASI SAMPAH DOMESTIK DAN KARAKTERISASINYA - Etty Marti Wigayati; Muljadi Muljadi (Jurnal Ecolab, 2008)
Garbage problems are increasing day by day. Garbage problems may generate environmental pollution problemswith its impact are continued to be increased. One of the technology to destroy the garbage is by incinerator. Thestudy was trying to reuse the ash resulted from the incineration of garbage by incinerator which have an addedvalue. The ash composition was similar as clay, so the ash could be used as a raw material for making batako whichare the weight ratio between sand and comment was 3:1. Some of sand was substituted by ash from incinerator withcompositions of 0%, 10%, 20%, 25%, and 30%. All the raw materials were homogenously mixed, and then wereformed by casting and were dried in open air variation of time between 7 days and 28 days. The resulting dried batakowere characterized for its density as indicated the decreasing density was in line with the increasing of ash assubstituted and the drying time of 28 days gave result the bigger one. The porosity value decreased along with theash content and giving the smallest one after drying 28 days. The water absorption value will decreased along withthe increasing ash content and the longer time of drying process. The bending and compressive strength value weregrowing larger with increasing ash content, and by giving 25% ash, the compressive strength value became stabilized.Comparing to the existing batako market, batako using incinerator ash gave better quality.